The role of The Iraq’s ancient schools in transferring knowledge: from the specialized professors’ viewpoint - Al-Guzaie, Alla Ibrahim Sarhan (Al-Adab Journal, 2021)
The current research aimed to identify 1-The role of The Iraq’s ancient schools in transferring knowledge from the specialized professors’ viewpoint. 2-The statistical differences significance in the role of The Iraq’s ancient schools in transferring knowledge from the specialized professors’ viewpoint according to the variable of certificate and specialization. To achieve these goals, a sample of 200 professors were selected from the history and archeology professors from Al-Qadisiyah, Kufa, Baghdad and Mosul universities for the academic year 2019-2020. They were chosen randomly. The researcher made a questionnaire to know the role of The Iraq’s ancient schools in transferring knowledge and after getting the psychometric characteristics of veracity and constancy, the questionnaire composed of (20) items, and after applying the questionnaire on the sample, it became clear that there is a role of The Iraq’s ancient schools in transferring knowledge. The results also showed statistically significant differences according to the variable of specialization and for the history professors and based on these results the research came out with a set of recommendations and suggestions.